Effect of Initial Handling Training in Accidents on Knowledge of Fracture Handling in Pelamonia Institute of Health Sciences Students - Samsir; Hasbullah; Nurun Salaman (Formosa Journal of Science and Technology, 2023)
Community knowledge about the initial treatment of broken bones is minimal, generally people bandage using improvised, non-sterile cloth and immediately move the victim to the side of the road without knowing the complications of the broken bone if the assistance given is not appropriate. This study aims to determine the effect of early treatment training in fracture cases. This research was conducted with a pre-experimental with one group pre post test design. The sample of this research was 50 students of Bachelor of Nursing study program level 2 IIK Pelamonia who understood the knowledge of fracture management. Data analysis was tested using the Wilcoxon Test to compare the results of the pre test and post test. The results of the study based on statistical tests obtained a p-value of 0.0001 p <0.05. In conclusion, there is an effect of training in initial handling of fracture cases on knowledge of fracture management.